Evaluación de la estrategia de la marisquería como en Manabí de la ciudad de Babahoyo - Medina Vite, José Manuel (2021)
The Evaluation of the Strategies in the Seafood Restaurant "Como en Manabí", considers among its various processes using efficiency in terms of competition and the decrease in sales that it has to resort to all possible means to meet its goals or also remain, exploratory methodology was used, the survey technique was carried out to which it is directed to the target audience, in order to know the current situation of the elements causing the problems that occur in Marisquería "Como en Manabí" ; among which are; low level of sales, ignorance of the management of social networks, little publicity of the business, pandemic covid-19, among many other factors that were used to make the conclusions of the case.